Caribbean Report 20-10-1995 - Orr, Carol (anchor); Roberts, Andy (interviewee); Alfonso, Miguel (interviewee); Lewis, Nicole (correspondent); Perez, Ninoska (interviewee); Sanchez Parodi, Milton (interviewee); Estupinan, Mercedes (interviewee); Fraser, Tony (correspondent); Crosskill, Hugh (correspondent); Bond, Julian (interviewee); Walters, Ron (interviewee); Powell, Colin (interviewee); et al. (The British Broadcasting Corporation, 1995)
In this report the West Indies cricket team experienced a fifty run defeat at the hands of Sri Lanka in the Champions Trophy tournament in Sharjah. As the US approved the watered-down Helms-Burton bill, Cuban Ministry spokesman Miguel Alfonso states that this was totally unacceptable. In Miami, Cuban exiles give their reaction to the anti-Cuba bill. In Trinidad and Tobago, an unconfirmed number of candidates signed nomination papers for the upcoming general elections as Prime Minister Patrick Manning exudes confidence in his party. After the Million Man March in Washington, one clear beneficiary is the controversial organizer Louis Farrakhan as fellow black leaders are forced to take a fresh look at him. Development consultant Atherton Martin comments on whether there should be a regional approach to encourage black leaders to at least be sensitive to the Caribbean agenda. The 11th Non-Aligned Summit was declared a major success with proposals to limit the scope of UN peacekeeping operations and for developing nations to be given a great say on the UN Security Council. In Britain, the Trade Union Congress has organized a march against racism to be held in Manchester.
1. Headlines with Carol Orr (00:00-00:29)
2. The West Indies cricket team crash to a fifty run defeat (00:30-02:36)
3. Officials in Havana and exiles in Miami in conflict over proposed anti-Cuban legislation (02:37-06:24)
4. Nomination day in Trinidad and Tobago and Prime Minister Manning feels confident (06:25-08:11)
Keywords: Cricket -- West Indies; Cricket -- Tournaments -- Sri Lanka; Economic sanctions, American -- Cuba; Embargo -- Cuba; Cuban Americans -- Florida -- Miami; Exiles -- Florida -- Miami; Political candidates -- Trinidad and Tobago; Trinidad and Tobago -- Politics and government; African American leadership; African Americans -- Race identity -- United States; African Americans -- Politics and government; Blacks -- Caribbean Area; African Americans -- Relations with Caribbean; Peacekeeping forces; Developing countries -- Influence; Racism -- Great Britain; Great Britain -- Race relations; United Nations -- Reform